Rethinking Rural Literacies: Transnational Perspectives (Book Review) - Simone White (Journal of Research in Rural Education, 2014)
Perspectives co-edited by Bill Green and Michael Corbett, brings together intern ational scholars from two distinctive fi elds"rural education and literacy studies"to provide scholarly insights into the role and signifi cance of literacy practice and education in and for rural social development. Collectively the chapters seek to explore and contribute to a deeper understanding of how such notions as "literacies," "education," "social justice," "rurality" and "placeconsciousness" together might better serve our world. What emerges from the chapters in this book is that there is indeed "no essential rural" (p. 8) and yet across and between the chapters a greater sense of rurality is intimately evoked.